Contiguous U.S. surface water availability and short-term trends of wastewater effluent flows in San Antonio, TX. (October 2020) - Siddiqui, Samreen; Conkle, Jeremy L.; Sadovski, Alexey
Abstract: Surface water is a vital and sometimes stressed resource in the U.S. The quantity of this resource is threatened by population shifts and growth concurrently with climate change intensification. Additionally, growing population centers can impact water quality by discharging treated wastewater effluent, which is typically of lower quality than its receiving surface waters. Depending on baseflow and environmental factors, this could decrease water quality. From a previous model prepared in our lab, this study can improve the understanding of water resource quality and quantity, surface water availability for the contiguous U.S. was estimated for each USGS Hydrologic Unit Code (HUC) during 2015. The Mississippi River generally served as a dividing line for surface water availability, with five of the six regions with very low water availability (<24, 000 LD −1 Km −2 ) residing in the west. These same areas also experience more drought as well as more severe droughts than regions in the east. In regions with lower surface water flows, their water quality is more susceptible to the influence of wastewater effluent discharges, especially near large and growing population centers like San Antonio, Texas. A prediction model was established for this city, which found that from 2009 to 2017 wastewater effluent increased by 1.8%. As cities grow, especially in the Southwest and Western U.S. together with intensified climate change, surface water quantity and quality become more crucial to sustainability. This study shows where surface water availability is already an issue and provides a model to estimate, as well as project, wastewater effluent flows into surface water bodies. Graphical abstract: Image 1 Highlights: Water availability for Continental U.S. during 2015 was calculated. Lowest hydrological unit code (HUC) regions with low water availability were identified: HUC 1, 15, 16, 17, and 18. These same HUC areas also experience more drought as well as more severe droughts than regions in the east. Wastewater effluent flow from San Antonio, TX region increased by 1.8% from 2009 to 2017.